IMPACT OF PMKVY ON PRODUCTIVITY OF YOUTH IN CHENNAI REGION: A SOCIOECONOMIC ANALYSIS (CAHIERS MAGELLANES-NS, 2024)
The Pradhan Mantri Kaushal Vikas Yojana (PMKVY) is a pivotal initiative by the Government of India aimed at enhancing the skills and employability of youth across the country. This research paper investigates the impact of PMKVY specifically on the productivity of youth in the Chennai region, analysing socioeconomic factors that influence skill development outcomes. The study utilizes a mixed-methods approach, integrating quantitative analysis of employment and income data with qualitative insights from stakeholder interviews. The findings suggest that while PMKVY has positively influenced youth productivity in Chennai, challenges such as skill-job mismatches and regional disparities persist, necessitating targeted policy interventions for sustainable socioeconomic development.